Affectionate Interactions of Cats with Children Having Autism Spectrum Disorder - Hart, Lynette A.; Thigpen, Abigail P.; Willits, Neil H.; Lyons, Leslie A.; Hertz-Picciotto, Irva; Hart, Benjamin L. (Frontiers in Veterinary Science, 2018)
Mental and physical benefits of dogs have been reported for adults and children with special needs, but less is known about benefits of cats for children. A cat that can be held by a child could provide important therapeutic companionship for children with severe or less severe autism spectrum disorder (ASD) who otherwise may lack prosocial behaviors. Because relatively little is known about the behavior of cats around children, we conducted this study. Phase 1 gathered web-survey data from families having an adult cat and a child with ASD (n = 64). In Phase 2, there were direct telephone interviews of parents having a child with severe ASD (n = 16) or less severe ASD (n = 11), or typical development (n = 17). From the Phase 1 web survey of families with ASD children (full range of severities), affectionate interactions of the cats with children were common. Most parents with ASD children volunteered positive comments regarding the cat, such as calming the child, being a soothing protector or a guardian. In the interviews in Phase 2, for all three groups, most parents characterized cats as at least moderately affectionate toward the child. However, cats living with severe ASD children were reported to exhibit less affection than those living with typically developing children or children with less severe ASD. A minority of cats in each group showed some aggression to the specified child; this was not elevated with ASD children. Responses suggested that the cats adopted as kittens were more affectionate and less aggressive to all categories of children than those adopted as adults. Overall, participants reported that ASD children’s behaviors indicated that they valued the relationship with the cat, similar to typically developing children, pointing to the importance and potential usefulness of selecting affectionate and compatible cats for ASD children.